On the Analogical Suffixation of Paired Antonyms: The Case of English innie and outie. - SÁNCHEZ FAJARDO, JOSÉ A. (Atlantis (0210-6124), 2020)
In English, there are a series of paired antonyms ending with the same suffix, particularly in slang or colloquial speech--stardom, regulardom/unknowndom; friendship, enemyship; singlehood, marriedhood, etc. This article looks into the tenets of the analogical suffixation of paired antonyms (ASPA), which is the process that is thought to underlie the mechanisms of morphological analogy and semantic complementation in the structuring of same-suffixed antonymic pairs (APs). In the study of ASPA, the AP innie/outie is used to explore the interconnection of antonymy, suffixation and analogy in the twenty-nine senses identified in the corpora (News on the Web Corpus and Lexis Nexis Academic). This case study shows that the semantic composition of the AP is the result of overlapping categories that involve the bases (in-, out-), the attached suffix (-ie/y), the complementary and coalescent nature of the pairs and the morphological adaptation undergone by the etymons to fit into the pairing markedness. The process of ASPA is a universal and scalar property that depends on the semantic opacity of bases, the sociolinguistic value of the word stock and the concept of lexical creativity. The examination of the morphological analogy of paired antonyms can shed more light on the predictability and performance (profitability) of word-formation mechanisms in both mainstream and peripheral lexis.